Measuring Problematic Facebook Use among Adolescents and Young Adults with the Bergen Facebook Addiction Scale: A Psychometric Analysis by Applying Item Response Theory - Primi, Caterina (Int J Environ Res Public Health, 2021)
The Bergen Facebook Addiction Scale (BFAS) is widely used, but psychometric evidence by applying Item Response Theory (IRT) is lacking. Considering the advantages of this psychometric approach, the aim of study was to investigate the psychometric properties of the Italian version of the BFAS among adolescents and young adults. Participants were 1134 (50% males, Mean age = 20.7, SD = 3.5, range = 14–33 years) Italian high school students and undergraduates. The unidimensionality of the scale was confirmed (χ(2)/df = 2.8, CFI = 0.99, TLI = 0.98, and RMSEA = 0.04 [C.I. = 0.02–0.06]) and IRT analysis showed that the scale assesses medium and high levels of the trait, and that it is useful in order to discriminate different levels of Problematic Facebook use (PFU) within this range of trait, in which the scale is sufficiently informative. The relationships of BFAS θ scores with theoretically related constructs provided support to the validity of the scale. In accordance with previous studies, BFAS scores were positively correlated with Problematic Internet use and problematic Social Network use, negatively correlated with self-esteem, and positively related to loneliness. The Differential Item Functioning (DIF) analysis showed that BFAS is invariant across gender, and only one item had uniform and small-in-size DIF. Additionally, we tested age invariance. Since only 17% of the BFAS items were non-invariant, we determined that the BFAS exhibited minor non-invariance as a whole. An analysis of the adequacy of the polythetic and monothetic criteria to define the range of the trait indicative of problematic use was also conducted. Overall, this study offers evidence that BFAS is a valuable and useful scale for measuring high levels of PFU among Italian adolescents and young adults.